Jenis – Jenis Amphibi (Ordo Anura) di Kecamatan Palangga Selatan Kabupaten Konawe Selatan Sulawesi Tenggara - Nasarudddin Nasarudddin; Wa Ode Harlis (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACT Amphibious existence of the habitat is influenced by several types of habitats eg rice fields, rivers, swamps and secondary forests. South Palangga is a region located in Konsel which has several ecosystems such as forests, savannahs, swamps and mangrove forests. So far the scientific information related to the presence Konawe amphibious species in the South, particularly in the district of South Palangga still very minimal, so it takes a more comprehensive scientific studies related to the presence of wildlife. Destination of the study is to determine the type of amphibious -type (Order: Anura) in the district of South Palangga Privinsi Southeast Sulawesi. The method used is the method VES (Visual Encounter Survey) is a way down both sides of the river and the rice fields and record types of amphibious found. This research was conducted 2 stations 2 stations river habitat and habitat fields. The research result was 606 people composed of 8 types and four families are Bufonidae, Dicroglossidae, Ranidae, and Rhacophoridae.Keywords: Diversity, Amphibian, Habitat, Southern Palangga